(untitled) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2017)
The book under review is a collection of 27 articles of Elisabeth Piirainen published from 1994 to 2013 in various journals and edited volumes. The collection unites four major research topics of the author: phraseology of dialects, areal phraseology, contrastive phraseology and research into widespread idioms. All these research topics are characterized by application of strongly empirical methods of questionnaires surveys among native speakers (with and without professional background in linguistics) as well as the theoretical apparatus of cognitive semantics and cultural semiotics. Instead of discussing each article individually, I would rather group them around the research areas mentioned above and focus on the main findings that underline the importance of both these topics as such and of the article collection under review.